Impact of ongoing intravenous thrombolysis until completion of endovascular treatment in large vessel occlusion stroke patients - Wischmann, Johannes; Pradhan, Cauchy; Zimmermann, Hanna; Keidel, Linus; Tiedt, Steffen; Dimitriadis, Konstantinos; Liebig, Thomas; Höglinger, Günter; Kellert, Lars (Frontiers in Neurology, 2023)
Background Recent studies have implied that ongoing intravenous thrombolysis (IVT) during endovascular treatment (ET) improves functional outcomes in patients who have undergone stroke caused by a large vessel occlusion (LVO). In this study, we investigated the effect of ongoing IVT until completion of ET on procedure duration, first-pass thrombectomy rate, and periprocedural complications. Methods We analyzed patients from the German Stroke Registry-Endovascular Treatment dataset, collected between June 2015 and December 2021. Primary outcomes were modified Rankin Scale (mRS) score after 3 months and achievement of a Thrombolysis In Cerebral Infarction (TICI) score of 2b-3. Secondary parameters included ET duration, first-pass thrombectomy, and periprocedural complications. Results Of the 13,082 patients in the dataset, 1,639 met the study inclusion criteria. A total of n = 317 patients (19.3%) underwent ongoing IVT until completion of ET, while IVT was completed prior to ET in 1,322 patients (80.7%). Ongoing IVT was associated with higher rates of achievement of an mRS score of 0–2 (or a back-to-baseline) after 3 months [odds ratio (OR) 1.53; 95% confidence interval (CI) 1.08–2.17]. Furthermore, ongoing IVT was predictive of achievement of a TICI score of 2b-3 (OR 1.37; 95% CI 1.03–1.83) and of first-pass thrombectomy (OR 2.07; 95% CI 1.51–2.84), while reducing the rate of peri-interventional complications (OR 0.64; 95% CI 0.44–0.94) and reducing ET duration by 24 min [β = −24.35; 95% CI −32.92–(−15.79)]. Conclusion Our findings suggest that ongoing IVT until ET completion has a favorable impact on both clinical and angiographic outcomes, as well as on periprocedural conditions, regardless of the overall time intervals involved. Therefore, rapid ET after IVT should be sought in order to take advantage of the additive effect of ongoing IVT during ET. Future studies should consider IVT timing in the context of ET as a potential confounder and treatment target.